EVALUASI PENGELOLAAN EKOSISTEM MANGROVE PADA DAERAH PERLINDUNGAN LAUT DI DESA BLONGKO, KECAMATAN SINONSAYANG KABUPATEN MINAHASA SELATAN PROVINSI SULAWESI UTARA - Joshian N.W. Schaduw (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2016)
ABSTRACT Mangrove ecosystem in Blongko village has many functions for coastal area. The aims of this research was to describe potential and the existing condition of mangrove ecosystem and also to give directive policy strategic for conservation mangrove ecosystem in this area. This research used primary and secondary data. Primary data was gathered by field observation and in-depth interview with 100 respondens by questionnary. Secondary data was gathered by unravel various literature and related institution. The development indicators was used to determine the policy strategic of sustainable mangrove ecosystem. Its was threat, factor, and constraint causing degradation mangrove ecosystem. This research got three policy strategy to carry on of sustainable mangrove ecosystem. Its was increase of human resources quality, protection and continuation of mangrove ecosystem, and low and institution reinforcement. This strategy was expected to depress degradation in mangrove ecosystem. Keywords : Coastal Area; Blongko village; Mangrove Ecosystem; Policy Strategy.